(untitled) (KULT_online, 2012)
After having taken place, theatre productions and performances usually are lost irretrievably. How then can they be approached on a historical level? In their excellent book Theaterhistoriografie: Eine Einführung (Theatre Historiography: An Introduction), the three German theatre scholars Jan Lazardzig, Viktoria Tkaczyk, and Matthias Warstatt present relevant theoretical perspectives, methods, and manners of presentation for theatre historiography. This way, they equip readers with essential instruments and tools for their own research.